(untitled) (United States, 1997)
Part 1:Contains reference articles on fundamentals of architecture and design, including universal and accessible design, architectural ethics, bioclimatic design... Part2: Contains design data on all aspects of architectural design and building construction, including substructure, superstructure, building shell, interiors, and services. The appendix: Includes tables and reference, classic reference articles from former editions of time-saver standrds,and introduction.
Keywords: Architectural design,Building,Building; Handbooks, manuals,Standards